Analisis Faktor-Faktor Yang Memengaruhi Keputusan Pembelian Produk Halal Pada Gerai Pempek Nony 168 Palembang - Puspa Dewi; Adryan Rachman (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The growth of the Muslim population in Indonesia has strengthened public awareness regarding halal food, making this issue increasingly important in the culinary industry. However, complexity in the process of making halal certification is often faced, especially by small and medium scale producers, who consider the process of making halal certification a complex challenge and require expensive costs. The aim of this research is to determine the influence of brand awareness, product quality and brand image on consumer purchasing decisions for halal products. The data collection technique uses a questionnaire. Samples were taken using the Non Probability Sampling Technique with the Purposive Sampling method which was distributed to 115 respondents from consumers of Pempek Nony 168 Palembang. This research uses testing tools in the form of SmartPLS 3.0 software with the PLS-SEM analysis method. The research path coefficient results show that product quality has a positive and significant influence on brand loyalty, but brand awareness does not have a positive and significant influence on brand loyalty. Apart from that, brand awareness and brand loyalty have a positive and significant influence on purchasing decisions, but product quality does not have a positive and significant influence on purchasing decisions.